2017
DOI: 10.1123/ijspp.2016-0594
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Mechanical Stiffness and Relationships to Performance Determinants in Middle-Distance Runners

Abstract: In well-trained MD athletes, greater stiffness appears linked to faster and more economical running. Although k had the strongest relationship with RE, k while sprinting and k in maximal unilateral jumps may be more practical measures of stiffness. Agreement between global stiffness assessments and k highlights the energy contribution of the Achilles tendon to running efficiency and velocity. Further research incorporating these assessment tools could help establish more comprehensive mechanical and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…27,28 Nevertheless, other studies have shown that middle- and long-distance runners with the best running economy or the best records had stiffer ATs. 14,41 Thus, there is no clear relationship between AT stiffness and performance. Because of the nature of the triceps sural MTC and its function in the storing and releasing of elastic energy, no difference in AT stiffness may facilitate this function, and it could be explained by the interaction between muscle and tendon during movement.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Nevertheless, other studies have shown that middle- and long-distance runners with the best running economy or the best records had stiffer ATs. 14,41 Thus, there is no clear relationship between AT stiffness and performance. Because of the nature of the triceps sural MTC and its function in the storing and releasing of elastic energy, no difference in AT stiffness may facilitate this function, and it could be explained by the interaction between muscle and tendon during movement.…”
Section: Discussionmentioning
confidence: 99%
“…A novel contribution from our study was the analysis of the potential benefits of beetroot juice ingestion on different biomechanical variables that has been linked to running performance in the literature, such as leg stiffness [ 23 , 30 ]. For example, leg stiffness has showed to be negatively associated with running economy, since, in theory, a stiffer lower limb would store a higher amount of elastic energy that would assist in the force production during running and, therefore, it would reduce the cost of the exercise [ 9 , 23 ]. Results in our study showed trivial effects of beetroot juice supplementation in leg stiffness, similar to submaximal running economy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 20 ] observed that 8 days of beetroot supplementation didn’t increase performance variables in elite 1500m runners; however, whether larger interventions might have benefits in elite populations is unknown. Moreover, to the best of our knowledge, no studies have analyzed the potential effects of beetroot supplementation in mechanical aspects of running such as leg stiffness, a variable that has been linked to running economy in different studies [ 21 23 ]. For this, the purpose of this study is to analyze the physiological, psychological and biomechanical effects of beetroot juice supplementation in elite distance runners.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to elite runners in the study of sprinting 26 and triathlon 27 , but it has not been systematically examined in elite middle distance runners. Rogers and colleagues studied leg stiffness in a group of highly-trained middle distance runners (average 1500 m best: 4:02) at a single submaximal speed (14 km/h) and at a maximal sprinting speed and observed that the leg stiffness in sprinting was strongly correlated to both running economy and maximal sprinting speed 28 . Similarly, Fourchet and colleagues studied the spring-mass characteristics of youth middle distance runners during an exhaustive run and found contact time, vertical displacement, and leg compression to increase following the run, resulting in decreased leg stiffnesses with consistent stride lengths and frequencies 29 .…”
Section: Introductionmentioning
confidence: 99%